Blockade of α2-adrenoceptors induces Arc gene expression in rat brain in a glutamate receptor-dependent manner: a combined qPCR, in situ hybridisation and immunocytochemistry study. - Serres, F; Rodriguez, M; Rivet, J; Galizzi, J; Lockhart, B; Sharp, T; Millan, M (2012)
Studies of 5-HT-glutamate interactions suggest that activation of brain 5-HT(2A) receptors leads to an AMPA receptor-mediated induction of the immediate early (activity-dependent) gene, Arc (Arg3.1). In this respect, noradrenaline-glutamate interactions are poorly characterised. Here we investigated the influence on regional brain Arc gene expression of selective blockade of α(2)-adrenoceptors in rats. Several complementary techniques were used: qPCR (mRNA, discrete tissue punches), in situ hybridisation (mRNA, sections) and immunocytochemistry. The α(2)-adrenoceptor antagonist, RX 821002, dose-dependently and time-dependently (maximal effect 2 h) increased Arc mRNA levels as demonstrated both by qPCR and in situ hybridisation. The α(2)-adrenoceptor antagonist, atipamezole, also increased Arc mRNA in in situ hybridisation studies. Changes in Arc mRNA after RX 821002 were of similar magnitude in punches and intact tissue sections and region-specific, with effects being most pronounced in parietal cortex and caudate putamen, less robust in frontal cortex, and not detectable in hippocampal sub-regions. Both qPCR and in situ hybridisation studies demonstrated that RX 821002-induced Arc mRNA was blocked by the AMPA antagonist, GYKI 52466. Pretreatment with the NMDA antagonist MK 801 also prevented RX 821002-induced Arc mRNA, as did the mGluR5 antagonist MPEP, whilst the mGluR2/3 antagonist, LY341495, had no effect. Finally, immunocytochemical studies showed that RX 821002 increased Arc-immunoreactivity in cells in close apposition to α(2)-adrenoceptor-positive processes. Thus, employing three complementary techniques, these observations demonstrate that blockade of α(2)-adrenoceptors triggers brain expression of the immediate early gene, Arc, and that this effect involves the recruitment of AMPA, NMDA and mGluR5 but not mGluR2/3 glutamatergic receptors.